Amplicon sequencing analysis of arbuscular mycorrhizal fungal communities colonizing maize roots in different cover cropping and tillage systems - Masao Higo (Nature Portfolio, 2020)
Abstract Our understanding regarding the influence of intensive agricultural practices, including cover cropping and tillage, on communities of arbuscular mycorrhizal fungi (AMF) is lacking. This would prove to be an obstacle in the improvement of current maize (Zea mays L.) production. Therefore, using amplicon sequencing, we aimed to clarify how AMF communities and their diversity in maize roots vary under different cover cropping systems and two types of tillage (rotary and no tillage). Two kinds of cover crops (hairy vetch and brown mustard) and fallow treatments were established with rotary or no tillage in rotation with maize crops. Tillage and no tillage yielded a set of relatively common AMF operational taxonomic units (OTUs) in the maize crops, representing 78.3% of the total OTUs. The percentage of maize crop OTUs that were specific to only tillage and no tillage were 9.6% and 12.0%, respectively. We found that tillage system significantly altered the AMF communities in maize roots. However, the AMF communities of maize crops among cover cropping treatments did not vary considerably. Our findings indicate that compared with cover cropping, tillage may shape AMF communities in maize more strongly.